A prospective randomized double-blind study comparing dexmedetomidine vs. combination of midazolam-fentanyl for tympanoplasty surgery under monitored anesthesia care - Devangi A Parikh; Sagar N Kolli; Hemangi S Karnik; Smita S Lele; Bharati A Tendolkar (Wolters Kluwer Medknow Publications, 2013)
Background: Analgesia and sedation are usually required for the comfort of the patient and surgeon during tympanoplasty surgery done under local anesthesia. In this study, satisfaction scores and effectiveness of sedation and analgesia with dexmedetomidine were compared with a combination of midazolam-fentanyl. Materials and Methods: Ninety patients undergoing tympanoplasty under local anesthesia randomly received either IV dexmedetomidine 1 μg kg -1 over 10 min followed by 0.2 μg kg -1 h -1 infusion (Group D) or IV midazolam 0.06 mg kg -1 plus IV fentanyl 1 μg kg -1 over 10 min (Group MF) followed by normal saline infusion at 0.2 ml kg -1 h -1 . Sedation was titrated to Ramsay sedation score (RSS) of three. Vital parameters, rescue analgesics (fentanyl 1 μg kg -1 ) and sedatives (midazolam 0.01 mg kg -1 ), patient and surgeon satisfaction scores were recorded. Results: Patient and surgeon satisfaction score was better in Group D than Group MF (median interquartile range (IQR) 9 (8-10) vs. 8 (6.5-9.5) and 9 (8.5-9.5) vs. 8 (6.75-9.25), P = 0.0001 for both). Intraoperative heart rate and mean arterial pressure in Group D were lower than the baseline values and the corresponding values in Group MF ( P < 0.05). Percentage of patients requiring rescue fentanyl was higher in Group MF than Group D (40% vs. 11.1%, P = 0.01). One patient in Group D while four in Group MF (8.8%) required rescue sedation with midazolam ( P > 0.17). Seven patients in Group D had dry mouth vs. none in Group MF ( P = 0.006).One patient in Group D had bradycardia with hypotension which was effectively treated. Conclusion: Dexmedetomidine is comparable to midazolam-fentanyl for sedation and analgesia in tympanoplasty with better surgeon and patient satisfaction. Hemodynamics need to be closely monitored.